METODE SOSIODRAMA : UPAYA PEMBENTUKAN PERILAKU DALAM CERITA MALIN KUNDANG - Tengku Hafinda (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
This study aims to examine the application of the sociodrama method in Bungong Jeumpa Kindergarten in Malin Kundang's story about the formation of children's behavior. The type of research used is classroom action research with a quantitative design. The results showed that the application of the sociodrama method to the formation of children's behavior in the first cycle, teacher activities obtained an average number of 3 with high categories (75%), student activities obtained an average number of student activities of 2.5 medium categories (63%) , the average student discipline is 2.5 medium category (63%). Cycle II, the average teacher activity is 3.61 with the high category (87.5%) student activity obtaining an average number of student activities of 3.35 in the high category (84%) and the average number of student disciplines being 3.45 in the high category (86%). The Shiddiq indicator increased by 20%. Patience increased by 18.75%, Fairness increased by 20%, Sincerity increased by 20%, Trustworthiness and Keeping Promises increased by 20%. Meanwhile, the answer achievement increased by 25%. Overall, children's behavior increased by 20.625%. Keywords: sociodrama method, malin kundang story, noble character, children's behavior